2017
DOI: 10.31327/chalaza.v2i2.296
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Male Age on the Quality of Bali Cattle Fresh Semen

Abstract: This research was conducted by conducting experiments in UPTD laboratory of Livestock and Livestock Feeding Agricultural Service of Sulawesi Barat Province. The purpose of this research is to compare the age of males during March to April 2013. The results of this research are expected to be used as a guideline for the use of Bali Cattle research as a semen producer based on the age of livestock that can be used as one of the criteria in the selection of prospective semen producing males. The research material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Good quality semen is produced by superior bulls with good reproductive performance. Apart from the influence of genetic traits, it is stated that the qualified semen of the superior bulls can be influenced by several factors, such as the bull's age, temperature and season, ejaculation frequency, and nutrition (Nirwana and Suparman, 2017). Bulls with poor reproductive performance can affect the quality of the semen produced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Good quality semen is produced by superior bulls with good reproductive performance. Apart from the influence of genetic traits, it is stated that the qualified semen of the superior bulls can be influenced by several factors, such as the bull's age, temperature and season, ejaculation frequency, and nutrition (Nirwana and Suparman, 2017). Bulls with poor reproductive performance can affect the quality of the semen produced.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the age of bulls is one of the important factors that influence semen quality (Fuerst-Waltl et al, 2006;Mahmood et al, 2014;Argiris et al, 2018). Nirwana and Suparman (2017) reported that age can have a significant effect on semen for Bali bulls.…”
Section: Introductionmentioning
confidence: 99%
“…178x10 6 spermatozoa per ml (Novianti et al 2020). Sperm concentration is influenced by the age of the bulls (Nirwana and Suparman 2017;Bayu et al 2020) and the spermatozoa progressive motility in this study was 75%.…”
Section: Characteristics Of Fresh Semenmentioning
confidence: 42%
“…The Progressive semen motility in this study was higher than Bali cattle raised in Nusa Tenggara Timur with an individual movement average of 70% (MataHine et al 2014) and Balinese cattle raised in Sulawesi (Nirwana and Suparman 2017). This difference in progressive motility is caused by the age of different males (Bayu et al 2019).…”
Section: Characteristics Of Fresh Semenmentioning
confidence: 58%
“…Vitamin E or alpha-tocopherol is an antioxidant compound that serves to capture free radicals by providing the hydrogen atom on peroxyl radical (Alawiyah and Hartono, 2006;Wardly and Jeffrey, 2007;Romadhoni et al, 2014). Alpha-tocopherol is a fat-soluble antioxidant that protects PUFA, components of cells and cell membranes from free radicals (Fitriani, 2013).) Alpha-tocopherol has a effect to increase metabolism in the testicular tissue and better spermatogenesis to produce a normal morphology of spermatozoa.…”
Section: Vitamin E and Seleniummentioning
confidence: 99%